2006
DOI: 10.1186/gb-2006-7-8-r71
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish promoter microarrays identify actively transcribed embryonic genes

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. Zebrafish promoter microarray

The development and verification of a genomic microarray for ChIP-chip analysis of zebrafish genes is described.

AbstractWe have designed a zebrafish genomic microarray to identify DNA-protein interactions…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…More recently, ChIP-on-chip has been applied to early zebrafish embryos to investigate the binding of modified hi-stones within the genome. Initial studies confirmed that H3K4me3 binding was enriched at transcriptional start sites similar to findings in mammalian cells (Wardle et al, 2006). More recently, a similar approach was used to demonstrate that both H3K4me3 and H3K27me3 marks are deposited at developmentally regulated genes independently of transcriptional activation immediately prior to the onset of zygotic transcription in zebrafish (Vastenhouw et al, 2010).…”
Section: Introductionsupporting
confidence: 60%
“…More recently, ChIP-on-chip has been applied to early zebrafish embryos to investigate the binding of modified hi-stones within the genome. Initial studies confirmed that H3K4me3 binding was enriched at transcriptional start sites similar to findings in mammalian cells (Wardle et al, 2006). More recently, a similar approach was used to demonstrate that both H3K4me3 and H3K27me3 marks are deposited at developmentally regulated genes independently of transcriptional activation immediately prior to the onset of zygotic transcription in zebrafish (Vastenhouw et al, 2010).…”
Section: Introductionsupporting
confidence: 60%
“…Nevertheless, a noticeable difference in the distribution of H3K4me3 among species or cell types examined to date lies in the detection of a “dip” immediately upstream of the TSS in mouse and human cells [7], [10], [22], [29]. This dip is not apparent in the Xenopus ChIP-chip or ChIP-seq data [15], [16], nor in the zebrafish ChIP-chip data [17], [18] (this study). This difference is unlikely to be due to array design, in particular probe spacing, because that is very similar (80–92 bp) in the mouse [7], human [10] or zebrafish [18] (this study) arrays used.…”
Section: Discussionmentioning
confidence: 63%
“…Fortunately, transcriptome analysis and interactome mapping (Alexeyenko et al, 2010) along with new methodologies in zebrafish such as ChIP-chip (Wardle et al, 2006), more rapid transgenic construction techniques (Kwan et al, 2007), RNA-Seq (Wang et al, 2009), genome-wide quantitative trait loci (QTL) analysis (Waits and Nebert, 2011) and advances in morpholino technology (Shestopalov et al, 2007) can be expected to further accelerate knowledge of AHR biology, including the identification of new transcriptional targets and mechanisms underlying the diverse endpoints of TCDD toxicity (Alexeyenko et al, 2010; Waits and Nebert, 2011; Yoshioka et al, 2011). …”
Section: Resultsmentioning
confidence: 99%